Response of the Most Promising Wheat Genotypes with Different Nitrogen Levels - Rawal, N.; Chalise, D.; Khatri, N. (International Journal of Applied Sciences and Biotechnology, 2017)
Field experiments were conducted during winter seasons of 2013 and 2014 on the alkaline and silty loam soils of NWRP, Bhairahawa to study the interaction of the most promising wheat genotypes with different nitrogen levels under different agro-ecological zones and recommend the appropriate dose of nitrogen for newly released varieties. The experiment was laid out in split plot design: four nitrogen levels (0, 50, 100 and 150 kg/ha) as a whole plot and six wheat genotypes (BL 3623, BL 3629, BL 3872, NL 1008, NL 1055 and Vijay) as a sub-plot which were replicated three times. There was significant effect of varieties and nitrogen levels on plant height, number of spikes, thousand grain weight and grain yield in both the years. In first year, the highest grain yield of 3.35 t/ha was obtained from the application of nitrogen @ 150 kg/ha with the genotype BL 3872 which is followed by the genotypes BL 3623 (3.15 ton/ha) and NL 1055 (3.05 ton/ha). Similarly in second year, the genotype NL 1055 gave the highest grain yield of 4.01 ton/ha followed by genotypes BL 3629 (3.83 ton/ha) and BL 3623 (3.81 ton/ha) from the application of nitrogen @ 150 kg/ha. Based on two years results, it can be concluded that N was a limiting factor in the productivity of wheat. Nitrogen @ 150 kg per ha produced higher yield and yield attributing characters. Similarly, the wheat genotypes NL 1055, BL 3629, BL 3623 and BL 3872 were superior among the genotypes.